2001
DOI: 10.1128/iai.69.10.6382-6390.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transient Transgenic Expression of Gamma Interferon PromotesLegionella pneumophilaClearance in Immunocompetent Hosts

Abstract: Gamma interferon (IFN-␥

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…NK cell-derived IFN-␥ has been shown to be critical in the resolution of other bacterial infections (51,52). In the context of Lpn infection, a critical role of IFN-␥ has been demonstrated (13,53). We have confirmed and extended this finding by demonstrating a nonredundant role of IFN-␥-producing NK cells in the control of Lpn infection.…”
Section: Discussionsupporting
confidence: 76%
“…NK cell-derived IFN-␥ has been shown to be critical in the resolution of other bacterial infections (51,52). In the context of Lpn infection, a critical role of IFN-␥ has been demonstrated (13,53). We have confirmed and extended this finding by demonstrating a nonredundant role of IFN-␥-producing NK cells in the control of Lpn infection.…”
Section: Discussionsupporting
confidence: 76%
“…P. aeruginosa challenge in septic WT and IRAK-M -/-mice. Previous work from our laboratory has identified the importance of inflammatory cytokines and chemokines (e.g., TNF-α, IL-12, and the CXC chemokines macrophage inflammatory protein-2 [MIP-2] and IFN-γ-inducible protein 10 [IP-10]) to the innate immune response against bacterial pathogens in the lung (12)(13)(14)(15)(26)(27)(28)(29)(30)(31). We therefore examined…”
Section: Bacterial Clearance Following It P Aeruginosa Administratmentioning
confidence: 99%
“…In macrophages and other immune cells, ligation of TLRs leads to downstream proinflammatory cytokine production. Prior studies from our laboratory have demonstrated that TNF-α and Th1 cytokines, including IFN-γ and IL-12, are critical mediators of innate immunity, particularly against bacterial pathogens in the lung (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the i.t. administration of this adenovirus vector results in the intrapulmonary expression of IFN-␥ in a time-and dose-dependent manner, leading to beneficial effects on pulmonary clearance of L. pneumophila (27). IFN-␥, IL-12, TNF-␣, IFN-␥-inducible protein-10 (IP-10), monokine induced by IFN-␥ (Mig), KC, and MIP-2 Abs used in ELISA were obtained from R&D Systems.…”
Section: Reagentsmentioning
confidence: 99%